A study of purchase intention of international fast-fashion brands of Malaysian Gen Y consumers - Ong, Derek Lai Teik *; Lee, Wan Shan (2018)
Generation Y consumers have become increasingly fashion conscious, contributing to the growth of the fashion industry particularly with a keen interest in international fast-fashion bands. Underlined by the consumer behaviour expectancy theory and theory of planned behaviour this study seeks to investigate the factors of brand image, perceived quality and country of origin affecting their purchase intention. Purposive sampling of 200 online survey using Google Docs were targeted Generation Y respondents. Results from the Multi Linear Regression show that brand image and perceived quality of fast fashion brands in Malaysia are important to purchase intention of Generation Y and that country of origin does not play a significant role. The findings recommend that new and upcoming intentional brands have the ability to market on the same level playing field as established brands regardless of country so long as they can capture the strong brand image of the Generation Y consumers effectively.